cGMP-independent nitric oxide signaling and regulation of the cell cycle - Cintron Ana; Munson Peter J; Barb Jennifer J; Sittler Kelly J; Goldberg Ilana G; Myers Daniela E; Ma Penglin; Zhang Jianhua; Cui Xiaolin; McCoy J Philip; Wang Shuibang; Danner Robert L (BMC Genomics, 2005)
Abstract Background Regulatory functions of nitric oxide (NO•) that bypass the second messenger cGMP are incompletely understood. Here, cGMP-independent effects of NO• on gene expression were globally examined in U937 cells, a human monoblastoid line that constitutively lacks soluble guanylate cyclase. Differentiated U937 cells (>80% in G0/G1) were exposed to S-nitrosoglutathione, a NO• donor, or glutathione alone (control) for 6 h without or with dibutyryl-cAMP (Bt2cAMP), and then harvested to extract total RNA for microarray analysis. Bt2cAMP was used to block signaling attributable to NO•-induced decreases in cAMP. Results NO• regulated 110 transcripts that annotated disproportionately to the cell cycle and cell proliferation (47/110, 43%) and more frequently than expected contained AU-rich, post-transcriptional regulatory elements (ARE). Bt2cAMP regulated 106 genes; cell cycle gene enrichment did not reach significance. Like NO•, Bt2cAMP was associated with ARE-containing transcripts. A comparison of NO• and Bt2cAMP effects showed that NO• regulation of cell cycle genes was independent of its ability to interfere with cAMP signaling. Cell cycle genes induced by NO• annotated to G1/S (7/8) and included E2F1 and p21/Waf1/Cip1; 6 of these 7 were E2F target genes involved in G1/S transition. Repressed genes were G2/M associated (24/27); 8 of 27 were known targets of p21. E2F1 mRNA and protein were increased by NO•, as was E2F1 binding to E2F promoter elements. NO• activated p38 MAPK, stabilizing p21 mRNA (an ARE-containing transcript) and increasing p21 protein; this increased protein binding to CDE/CHR promoter sites of p21 target genes, repressing key G2/M phase genes, and increasing the proportion of cells in G2/M. Conclusion NO• coordinates a highly integrated program of cell cycle arrest that regulates a large number of genes, but does not require signaling through cGMP. In humans, antiproliferative effects of NO• may rely substantially on cGMP-independent mechanisms. Stress kinase signaling and alterations in mRNA stability appear to be major pathways by which NO• regulates the transcriptome.